Biometric surveillance in environmental protection: Legal, ethical, and social-psychological perspectives - Naseer Sabbar Lafta; Rasem Mseer Jasim; Samar Adnan Mahmoud Ali; Mysoon Ali; Ammar Abdulkhaleq Ali (Environment and Social Psychology, 2025)
Environmental protection is another area where biometric surveillance technologies have been employed to monitor illegal deforestation, poaching and industrial pollution. Though such systems lead to higher detection rates (by 22-36%), shorter response times (by up to 75%), their use has complex legal, ethical, and social-psychological issues. The study investigates governance structures, stakeholder views and community approval in a mixed method research design, which included legal analysis, three case studies, a survey (N = 1000; margin of error +-3%) and semi-structured interviews (N = 55: law enforcement = 20, policymakers = 15, environmental agencies = 10, civil society = 10). Consent and an ethics clearance were given to all participants. Findings indicate complete access to legal systems and perceived access to protections like encryption and privacy-by-design results in increased trust, compliance, and perceived legitimacy. These are most languorously held by the young, and most feeble by the old (65% and 45% as I have already indicated). The trans-regional analysis tells us that we simply cannot afford to be segregated on international standards. The modeling validation R2 values range was 0.71 to 0.82. Efficiency is not an issue in isolation, but it has been established that efficiency is a social issue, a trust issue, a fairness and transparency issue among the individuals employed in these institutions. This would include the elevation of the law and ethics and psychology to the same level in order to make good use of it.